Strategi Komunikasi Petugas Badan Pusat Statistik (BPS) Kota Bandung dalam Melaksanakan Sensus Penduduk 2020 Di Masa Pandemi Covid-19 - Dini Rahmawati; Yulia Sariwaty Syaripudin; Lingga Rahayu Nugraha (Syntax Idea, 2021)
The purposeof this research is to know the communication strategy conducted by the population census officer of the Central Bureau of Statistics of Bandung in enumeration of the population during the Covid-19 pandemic in September 2020. This study uses descriptive qualitative methods. This research was conducted from 1 to 15 September 2020 and located in Bandung Wetan Subdistrict, Cihapit Village as many as 8 RW consisting of 46 RT. The research data was obtained directly from the field, namely from the cacah population and census officers of the population. In addition, other data used is obtained from related literature. In this study, the authors directly engaged with census officers from the Central Bureau of Statistics bandung while carrying out enumeration. The results showed that there are community groups that can receive visits from census officials and there are also community groups that refuse. During enumeration, communication conducted with the group of residents who receive is like the usual communication but with the addition of following the health protocol that is to use masks, face shields, maintain distance, always use hand sanitizer and show free letter Covid-19. Meanwhile, communication made to residents who refused the visit of BPS officers is by phone and WhatsApp application. Thus, it can be concluded that in times of pandemic disease that is dangerous, the census program of the population is still carried out even though not all enumeration is done face-to-face but also using the media in order to communicate with the population